Financial literacy and consumer protection: A road map to digital financial access by SMEs in Kenya - Salome M. Musau; Stephen Muathe; Lucy W. Mwangi (The Journal of Entrepreneurial Finance (JEF), 2022)
This paper seeks to ascertain the influence of financial literacy and financial consumer protection on digital financial access. The objectives of the study were to find out the effect of financial literacy on digital monetary access, and to find out the effect of f consumer financial protection on digital access of finances of SMEs in Sub County of Ruiru in County government of Kiambu, Kenya. Financial Literacy Theory, Information Asymmetry Theory and Social Learning Theory are the theories that guided formulation of study's objectives. Descriptive research design was used with the population of interest comprising of all SMEs owners in Ruiru Sub County in Kiambu County. The sample size for the study was 384 respondents derived byFisher (1998) formula. Primary data as collected by use of questionnaires. Descriptive statistics of mean, frequency, percentages and standard deviation were used combined with inferential analysis of correlation as well as multiple regression to analyse the data. Findings of the study indicated that financial literacy and financial consumer protection significantly and positively influence on digital financial access of SMEs. The paper concluded that an improvement in the knowledge of financial products, developing a financial attitude towards the long term, debt management literacy of SME owner, financial product choice knowledge and having the ability to make informed decisions regarding finances generally improves digital financial access of SMEs.
Keywords: 650; Financial literacy; consumer protection and digital access